2021
DOI: 10.3390/app11062774
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic Acid and Polycaprolactone Blended Cosmetic Microneedle for Transdermal Hispidin Delivery System

Abstract: Microneedles (MNs) are a new system of effective drug delivery that create micron-sized pathways to the epidermis or upper dermis regions of the skin. In this study, we developed coated-type microneedles for direct hispidin delivery to the skin. Hispidin is a well-known plant-derived antioxidant component showing antitumor, anti-inflammatory, antiallergic, antiangiogenic, antioxidant, hypoglycemic, hypolipidemic, and immunomodulatory activities. Polymeric blends of polylactic acid (PLA) and polycaprolactone (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Sorption characteristics at room temperature do not appear for this film. The study was carried out at a temperature of 35 °C, since the intended possible applications of developed mixed PLA/PCL films assume their use in direct contact with human skin [ 57 , 58 ]. The structure of the OTOA molecule consists mainly of hydrophobic fragments and includes, along with low-polar ester groups, specific ozonide rings [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sorption characteristics at room temperature do not appear for this film. The study was carried out at a temperature of 35 °C, since the intended possible applications of developed mixed PLA/PCL films assume their use in direct contact with human skin [ 57 , 58 ]. The structure of the OTOA molecule consists mainly of hydrophobic fragments and includes, along with low-polar ester groups, specific ozonide rings [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study was carried out at a temperature of 35 °C, since the intended possible applications of developed mixed PLA/PCL films assume their use in direct contact with human skin [57,58]. The structure of the OTOA molecule consists mainly of hydrophobic fragments and includes, along with low-polar ester groups, specific ozonide rings [59]. Only for PLA/PCL film with 40% OTOA observed sorption characteristics were similar to those of PCL films.…”
Section: Water Contact Angle Water Sorption and Water Vapor Permeabil...mentioning
confidence: 99%
“…38 Recently, similar work by Lee et al demonstrated that PCL/PLA blends of varying concentrations could achieve microneedles with great mechanical strengths (up to 51.26 MPa) for the transdermal delivery of hispidin. 39 Understanding the degradation, solubility and biocompatibility of such structured materials is essential for wide ranging applications in controlled drug release and delivery and implantable medical devices. The presence of specific degradable functionalities within the polymer chain is crucial for degradation to occur and by varying the concentration of such functional groups, control over degradability and the rate of degradation can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Recently, similar work by Lee et al demonstrated that PCL/PLA blends of varying concentrations could achieve microneedles with great mechanical strengths (up to 51.26 MPa) for the transdermal delivery of hispidin. 39 …”
Section: Introductionmentioning
confidence: 99%